CALDERAS AND IGNIMBRITES IN THE UZON-SEMYACHIK AREA OF KAMCHATKA: NEW DATA FROM FIELD WORK ON THE SHIROKOE PLATEAU - Leonov V.L.; Grib E.N. (My University, 1999)
New evidence is reported on the geologic structure of the southern side of the Uzon-Geizernaya depression (Shirokoe Plateau). As a result of detailed geological mapping, the rocks composing the plateau were divided into six members of different depositional environments. It is concluded that before the formation of the present-day Uzon-Geizernaya Depression, there existed a large depression which obviously was combined with the Bolshoi Semyachik caldera which is now located southward. A detailed study of the stratigraphy and mineralogy of the ignimbrites in the Uzon-Geizernaya Depression suggested that their emplacement had been a long, complex, multiphase process. There are three ignimbrite units separated by lava flows and lake deposits. The ignimbrites of a basaltic andesite composition are suggestive of the participation of water in their formation and of the fact that an important role in the origin of the Uzon-Geizernaya Depression was played by relatively small explosions in pre-existing depressions that were partially filled with water.